Case study on whole effluent toxicity testing from bulky landfill leachate / Mohd Zikri Ibrahim - Ibrahim, Mohd Zikri (2015)
All the while, waste authorities either assume that they know enough about the bulky waste stream or that it is too insignificant to deserve attention. Bulky waste describes those solid waste materials having a large physical dimension such as appliances, furniture, large auto parts, trees, stumps, and in addition wooden pallets and waste tires. The Objectives of this study is to identify the whole leachate toxicity test from a selected bulky landfill and its effects to the environment. Leachate samples were collected from leachate pond (n=4) and the discharge point (n=4). Leachate characterized was carry out followed by whole leachate toxicity test using Cyprinus Carpio. The result for physic-chemical characteristics of leachate showed that all the parameter was compliance except manganese and chemical oxygen demand (COD). However the result for dose response relationship at leachate pond and discharge point for fish species Cyprinus Carpio showed that the toxicity in the leachate and discharge point to river water relatively higher with the increasing of the percent of concentration (%). Based on the result, it showed that there was a poor environmental management from the landfill operator and that may become the source of environmental contamination and would disrupt the aquatic ecosystem.